2013
DOI: 10.1016/j.ijgo.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes after second‐trimester genetic amniocentesis in Siriraj Hospital

Abstract: Second-trimester genetic amniocentesis resulted in 0.2% of total pregnancy loss within 4 weeks of testing. This information is essential for patient counseling before amniocentesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
1
7
1
2
Order By: Relevance
“…Studies show that the skill level of the health care providers performing screening has tremendous effects in reducing the risks and increasing the success of screening ( Anuwutnavin, Chanprapaph, Ruangvutilert, Eammatta, & Tontisirin, 2014 ; Welch & Poulin, 2003 ). The results of a review study using data from articles on amniocentesis and chorionic villus sampling showed that poor skills in using prenatal screening equipment and underestimating the real risks of screening have adverse consequences ( Mujezinovic & Alfirevic, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that the skill level of the health care providers performing screening has tremendous effects in reducing the risks and increasing the success of screening ( Anuwutnavin, Chanprapaph, Ruangvutilert, Eammatta, & Tontisirin, 2014 ; Welch & Poulin, 2003 ). The results of a review study using data from articles on amniocentesis and chorionic villus sampling showed that poor skills in using prenatal screening equipment and underestimating the real risks of screening have adverse consequences ( Mujezinovic & Alfirevic, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Muchos son los factores que podrían estar involucrados en las discrepancias entre los resultados encontrados en diferentes centros de diagnóstico prenatal. Las características de la población, la metodología utilizada, la edad gestacional de realización de los procedimientos y la institución donde ellos son ofrecidos pueden influir en la tasa de morbiletalidad asociada (5)(6)(7)34,35,42).…”
Section: Discussionunclassified
“…La Amniocentesis Tradicional (AT) fue el primer procedimiento invasivo utilizado para recolectar líquido amniótico destinado al análisis citogenético del feto. Se trata de una técnica relativamente simple cuya seguridad y confianza diagnóstica se encuentra bien establecida (1)(2)(3)(4)(5)(6). Aunque sea considerado patrón, el procedimiento es limitado pues sólo puede realizarse en el segundo trimestre del embarazo y la edad gestacional en que se encuentra la paciente cuando los resultados son suministrados varía entre las semanas 17 y 18 (7).…”
Section: Introductionunclassified
“…The possibility of fetal loss leads to problems in the acceptance of this procedure by both the mother and the physician. Rates of fetal loss have been reported as 0.3%-1% in different publications [4][5][6]. In the ACOG 2007 guidelines, fetal loss associated with amniocentesis was reported at rates of 1in 300-500 and these rates could be lower in experienced centres [7].…”
mentioning
confidence: 99%
“…In the ACOG 2007 guidelines, fetal loss associated with amniocentesis was reported at rates of 1in 300-500 and these rates could be lower in experienced centres [7]. It has been reported in previous studies that fetal loss associated with amniocentesis occurs particularly within 4 weeks of the procedure [5]. In this study, an evaluation was made of fetal loss, especially in the first 4 weeks after primary amniocentesis, and whether or not there was an increase in other complications.…”
mentioning
confidence: 99%